Technology Drivers of Innovation Competitiveness in Biotechnology Entrepreneurship in Gauteng, South Africa - Tile, Sibahle (University of the Witwatersrand, Johannesburg, 2024)
Biotechnology entrepreneurship is a rapidly growing field with significant potential for economic development and innovation. However, most of the existing empirical research in this field has been conducted in developed economies, which may not directly apply to the unique context of developing economies like South Africa. In developing countries, including South Africa issues related to human health, food security, renewable resources, and environmental sustainability that biotechnology solutions address are more prevalent, alongside challenges of socio-economic development, unemployment, and low global competitiveness. These challenges emphasize the significance of entrepreneurship, particularly biotechnology entrepreneurship, in developing countries. This study aimed to investigate the drivers influencing innovation competitiveness in biotechnology entrepreneurship and evaluate the relevance and effectiveness of technology push and demand-pull innovation of biotechnology entrepreneurship in Gauteng, South Africa. The research adopted a qualitative approach and was conducted through fourteen virtual one-on- one interviews with semi-structured questions. Purposive sampling was used to select biotechnology entrepreneurs involved in the agriculture and health biotechnology sectors with innovations in the biopharmaceuticals, agritech, agroprocessing medical devices and diagnostics industries. The data collected from the participants in the interviews was then thematically analysed to draw a conclusion based on the findings. Main findings included: key drivers influencing innovation competitiveness within the biotechnology entrepreneurship sector in South Africa, emphasizing access to the market, funding, government support, regulatory compliance, and specific market trends as crucial factors. Participants highlighted the significance of market access, government funding, and adherence to regulatory standards for innovation. Additionally, the study explored market, entrepreneurial, and technological capabilities essential for commercializing biotechnology innovations in Gauteng, stressing the importance of entrepreneurial acumen, market understanding, and technological proficiency. It also outlined key enablers such as a growing market and resource availability, alongside constraints like limited funding, skills shortages, and regulatory complexities. The study illustrated how challenges such as access to funding, skills shortages, and unrealistic regulatory standards hinder innovation within the technology push model, while opportunities such as a growing market and potential government support serve as enablers within the demand-pull model, fostering a conducive environment for innovation
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Biotechnology; Innovation competitiveness; Entrepreneurship; Commercialisation; Technology push; Demand pull; Bioeconomy; Innovation ecosystem; UCTD; SDG-8: Decent work and economic growth